GAMBARAN CEMARAN BAKTERI Staphylococcus aureus PADA LIPSTIK CAIR TESTER - Faris Monica; Ganea Qorry Aina; Dita Irianti Rukmana (LPPM STIKes Mitra Adiguna, 2023)
Liquid lipstick is a cosmetic that is often used by women. The presence of water content in the raw material for lipstick can be a good medium for microbial growth. The use of a liquid lipstick tester is likely to have a high number of germs because it often comes in direct contact with the user's skin and lips. This study aims to determine the presence of Staphylococcus aureus bacterial contamination in the liquid lipstick tester. This research is a descriptive research. The variable in this research is a single variable, namely Staphylococcus aureus bacteria in the liquid lipstick tester. The number of samples was 16 samples from cosmetic shops in markets and malls in the City of Samarinda. The results of this study found that 61% of the liquid lipstick tester samples were contaminated with staphylococcus aureus bacteria. It is recommended to the public to pay attention to personal hygiene so that they are not contaminated with Staphylococcus aureus bacteria by washing their hands or using an antiseptic either before or after trying the liquid lipstick tester.